2012
DOI: 10.1152/ajpgi.00019.2012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol feeding enhances miR-21 induction during liver regeneration while inhibiting proliferation in rats

Abstract: Liver regeneration is an important repair response to liver injury. Chronic ethanol consumption inhibits and delays liver regeneration in experimental animals. We studied the effects of chronic ethanol treatment on messenger RNA (mRNA) and microRNA (miRNA) expression profiles during the first 24 h after two-thirds partial hepatectomy (PHx) and found an increase in hepatic miR-21 expression in both ethanol-fed and pair-fed control rats after PHx. We demonstrate that the increase of miR-21 expression during live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 39 publications
1
46
0
Order By: Relevance
“…While most miRNAs identified have never been described in the context of liver disease, others such as miR-21, miR-155 and miR-214 have already been reported as regulators of key pathways in liver diseases. MiR-21 is known to regulate liver fibrosis24–26 and regeneration 27 28. MiR-155 has been described to be expressed in inflammatory cells in alcohol-induced liver disease29 and in animal models of alcohol intake 30.…”
Section: Discussionmentioning
confidence: 99%
“…While most miRNAs identified have never been described in the context of liver disease, others such as miR-21, miR-155 and miR-214 have already been reported as regulators of key pathways in liver diseases. MiR-21 is known to regulate liver fibrosis24–26 and regeneration 27 28. MiR-155 has been described to be expressed in inflammatory cells in alcohol-induced liver disease29 and in animal models of alcohol intake 30.…”
Section: Discussionmentioning
confidence: 99%
“…Variable expression of miR-21 has been described in different organ systems and diseases states (25). Indeed, in normal and malignant hepatocytes, miR-21 was shown to be a potent contributor of cell proliferation, but miR-21 induction is not sufficient to regulate cell cycle progression during liver regeneration, particularly in ethanol-fed rats (26). These diverse observations neces- sitate a clear definition of tissue injury-specific expression and function of miR-21 expression.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that miR-21 is an important negative regulator of apoptosis. Previous studies have shown that miR-21 can be down-regulated in vitro by alcohol in neural stem cell/ neural progenitor cells (NSC/NPCs) (Miranda et al, 2010), while chronic ethanol feeding enhances miR-21 induction during liver regeneration (Dippold et al, 2012). …”
Section: Discussionmentioning
confidence: 99%